2014
DOI: 10.1002/jcop.21611
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Ecology of Adolescent Problem Behavior: Contributions of Community Factors and Parental Monitoring

Abstract: Addressed the ecology of deviant peer involvement, antisocial behavior and alcohol use, utilizing publically available information for indices of community risk/protective factors. A geospatial model was developed, combining geographic data (census, crime proximity, race/ethnicity, transportation accessibility) with information gathered for individual adolescents/household, geo-coded by home address. Adolescent-report of delinquency, association with deviant peers, substance use, and parental monitoring was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Crime data were acquired for 2008 from the city of Seattle's publically available data portal (data.seattle.gov), with 911 incident calls (approximately 183,000) grouped into seven major crime areas: homicide, assault, larceny/stolen property, robbery, burglary, car theft/car prowl, and lastly, nuisance crimes (e.g., disturbance, narcotics), and weighted in order of severity, as previously described (Chainey & Ratcliffe, 2005; Gartstein et al, 2017; Gartstein, Seamon, & Dishion, 2014). Our approach included an examination of spatial autocorrelation for crime incident data - the degree to which a set of spatial features and their associated data tend to cluster in space (Craglia, Haining, & Wiles, 2000), because of potential for such clustering to inflate Type I error (Longley, Longley, Goodchild, Maguire, & Rhind, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crime data were acquired for 2008 from the city of Seattle's publically available data portal (data.seattle.gov), with 911 incident calls (approximately 183,000) grouped into seven major crime areas: homicide, assault, larceny/stolen property, robbery, burglary, car theft/car prowl, and lastly, nuisance crimes (e.g., disturbance, narcotics), and weighted in order of severity, as previously described (Chainey & Ratcliffe, 2005; Gartstein et al, 2017; Gartstein, Seamon, & Dishion, 2014). Our approach included an examination of spatial autocorrelation for crime incident data - the degree to which a set of spatial features and their associated data tend to cluster in space (Craglia, Haining, & Wiles, 2000), because of potential for such clustering to inflate Type I error (Longley, Longley, Goodchild, Maguire, & Rhind, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Crimes (i.e., homicide, assault, larceny/stolen property, etc.) were weighted in a linear progression – from least severe (e.g., car theft) to most severe (e.g., homicide), according to a previously reported procedure, summarizing all crimes within 1000 ft of the residence (Chainey & Ratcliffe, 2006; Gartstein et al, 2014). Thus, the CPI represents a weighted distribution of crime reflecting exposure at each participant's location (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, the findings from the current study indicated little to no growth in active and passive parental monitoring across middle childhood and adolescence in this diverse sample of families living in at-risk neighborhoods. This finding largely suggests that these families may engage in more consistent levels of monitoring strategies in order to counteract the risks and difficulties inherent in these environments (Burton & Jarrett, 2000; Gartstein et al, 2014; Supplee et al, 2007). This study also highlighted the importance of employing an ecological perspective and considering broader contextual factors when examining parental monitoring strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that a constellation of factors plays a crucial role in the developmental course of parental monitoring strategies over time (Odgers et al, 2012), and consideration of how these individual, parent, family, and contextual factors interact is warranted. Work by Tom Dishion and others has also enhanced our understanding of the multitude of negative child and adolescent outcomes associated with poor parental monitoring including antisocial behavior, substance use, and affiliation with deviant peers (e.g., Dishion, Bullock, & Kiesner, 2008;Dishion, Patterson, Stoolmiller, & Skinner, 1991;Fosco et al, 2012;Gartstein et al, 2014;Kiesner, Dishion, Poulin, & Pastore, 2009;Wang et al, 2011). Consideration of these factors may help further elucidate how family dynamics contribute to the development of effective parental monitoring and the many untoward consequences that result when difficulties are encountered in the parental monitoring process.…”
Section: Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation